A History of Manipulative Therapy - Pettman, Erland (Journal of Manual & Manipulative Therapy, Inc., 2007)
Manipulative therapy has known a parallel development throughout many parts of the world. The earliest historical reference to the practice of manipulative therapy in Europe dates back to 400 BCE. Over the centuries, manipulative interventions have fallen in and out of favor with the medical profession. Manipulative therapy also was initially the mainstay of the two leading alternative health care systems, osteopathy and chiropractic, both founded in the latter part of the 19th century in response to shortcomings in allopathic medicine. With medical and osteopathic physicians initially instrumental in introducing manipulative therapy to the profession of physical therapy, physical therapists have since then provided strong contributions to the field, thereby solidifying the profession's claim to have manipulative therapy within in its legally regulated scope of practice.